1996
DOI: 10.1007/s002530050778
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cations on the hydrolysis of lactose and the transferase reactions catalysed by β-galactosidase from six strains of lactic acid bacteria

Abstract: beta-Galactosidases from Lactobacillus delbruekii subsp. bulgaricus 20056, Lb. casei 20094, Lactococcus lactis subsp. lactis 7962, Streptococcus thermophilus TS2, Pediococcus pentosaceus PE39 and Bifidobacterium bifidum 1901 were partially purified. The rate of hydrolysis of lactose given by the predominant beta-galactosidase activity from each of the bacteria studied was in all cases enhanced by Mg2+, while the effect of K+ and Na+ differed from strain to strain. The beta-galactosidases from all strains also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 6 publications
1
37
0
1
Order By: Relevance
“…Various investigators reported that the activity of b-galactosidase was affected by metal ions (Reithel & Kim 1960;Garman et al 1996;Hung & Lee 2002;Kim et al 2003). Besides, it was reported that the ionic effects on the activity of b-galactosidase vary with substrates (Becker & Evans 1969).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Various investigators reported that the activity of b-galactosidase was affected by metal ions (Reithel & Kim 1960;Garman et al 1996;Hung & Lee 2002;Kim et al 2003). Besides, it was reported that the ionic effects on the activity of b-galactosidase vary with substrates (Becker & Evans 1969).…”
Section: Discussionmentioning
confidence: 96%
“…Purification and characterization of b-galactosidase, obtained from various species of molds and bacteria, are also documented (Rohlfing & Crawford 1966;Somkuti & Steinberg 1979;Itoh et al 1980;Smart & Richardson 1987;Ohtsuka et al 1990;Dumortier et al 1994;Cavaille & Combes 1995;Garman et al 1996;Hung & Lee 2002). It has been shown that the properties of b-galactosidase varied with microorganisms.…”
mentioning
confidence: 96%
“…Also, several b-galactosidases from B. bifidum were found to display transferase activity [59,84,103,105,108]. Dumortier et al [59] purified a transgalactosidase and from a diversity of monomeric sugars only glucose and xylose could act as acceptors for transgalactosidase, using lactose as donor.…”
Section: B-galacto-oligosaccharidesmentioning
confidence: 99%
“…The covariate analysis showed no significant effect (P = 0.4478) of the initial β-gal activity in the CCEs on the kinetic parameters. Shah and Jelen [25] and Garman et al [6] also reported substantial differences in the β-gal activity in several different LAB species. The K m and k cat values obtained for the Lb11842 CCE in the present study were broadly similar to those determined by a different methodology for the same CCE preparation during lactose hydrolysis in 10% skim milk [33].…”
Section: Monosaccharide Formationmentioning
confidence: 99%
“…The transferase reactions have been described for highly purified β-gal preparations obtained from a number of microbial sources [6,11,20,27,29,31]. Using β-gal in the batch mode was suggested for maximization of oligosaccharide production [22].…”
Section: Introductionmentioning
confidence: 99%